2010
DOI: 10.1111/j.1467-9604.2010.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I was confident about teaching but SEN scared me’: preparing new teachers for including pupils with special educational needs

Abstract: This article is based on a research study undertaken with a small group of student teachers in an English university. They took part in a specialised school placement with pupils identified as having special educational needs, one of a range of current government initiatives designed to increase their capacity to work inclusively in schools. The students were placed in schools that were successful in working with children with special educational needs, undertaking set activities and tasks to increase their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…But, as the weeks go on, you start to get a relationship with the children and I think that, in itself, makes you more competent. You know what they’re capable of so you’re more like…yes, you’ve got a better relationship…it boosts your confidence (Brian FG4)First, these findings support those offered by Richards (2010), who suggested that the development of a strong, personal and trusting relationship with pupils with SEND can increase the confidence of prospective teachers. It is reasonable for us to argue, therefore, that when teachers are inducted into new school environments, time should be dedicated to developing relationships with pupils in order to increase teacher confidence.…”
Section: Findings and Discussionmentioning
confidence: 57%
“…But, as the weeks go on, you start to get a relationship with the children and I think that, in itself, makes you more competent. You know what they’re capable of so you’re more like…yes, you’ve got a better relationship…it boosts your confidence (Brian FG4)First, these findings support those offered by Richards (2010), who suggested that the development of a strong, personal and trusting relationship with pupils with SEND can increase the confidence of prospective teachers. It is reasonable for us to argue, therefore, that when teachers are inducted into new school environments, time should be dedicated to developing relationships with pupils in order to increase teacher confidence.…”
Section: Findings and Discussionmentioning
confidence: 57%
“…This can develop trainees' attitudes (Hodkinson 2020) and markedly improve their perspectives (Richards & Clough 2004; NASUWT 2008). It may also increase trainees' confidence (Richards 2010; Carter 2015; Coates et al . 2020), which can have an impact on self‐efficacy (Ekins et al .…”
Section: Exploring the Literaturementioning
confidence: 99%
“…Disparities exist regarding what trainees learn about SEND during their training (Richards 2010), largely due to time constraints, in terms of what must be achieved during 1‐year ITT courses (Carter 2015). This can result in ‘incidental learning’ (McIntyre 2009, 606) experiences, rather than thorough consideration of the planning and preparation required to meet the needs of pupils.…”
Section: Exploring the Literaturementioning
confidence: 99%
“…Near the start of the workshop I noted that I felt that many ‘mainstream’ classroomteachers were positively disposed towards inclusive education but felt lacking in confidence in their own professional skills to facilitate inclusive pedagogy (e.g. Richards, ) and that attitudes are more positive when teachers have had a chance to access to initial or further training in supporting children with SEN (e.g. Boyle et al ., ).…”
Section: Introductionmentioning
confidence: 99%